The prosecutor - Knight, Glenn, 1945- (Singapore : Marshall Cavendish, 2012)
Part autobiography, part casebook,but wholly the story of one man's fight for justice from both ends of the legal system. This book consists of real life accounts of well-known figures in the local legal and crime scene.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Knight, Glenn, -- 1944-; Public prosecutors -- Singapore -- Biography; Prosecution -- Singapore; White collar crimes -- Singapore